A systematic literature review of Aboriginal and Torres Strait Islander engagement with disability services. Issue 6 (23rd June 2022) - Trounson, Justin S.; Gibbs, Jordan; Kostrz, Krysia; McDonald, Rachael; Peters, Andrew
Abstract: This systematic review aims to identify the factors that facilitate or impede the engagement of Aboriginal people living with a disability with disability services through review of the current academic and industry literature. Aboriginal and Torres Strait Islander people are twice as likely to experience disability as non-Indigenous Australians, yet often have more difficulty accessing support. 17 documents were included in the final review. The review revealed the super-ordinate theme of culture and Indigeneity which pervades the three additional themes of accessibility, engagement and lack of support. All four themes can be viewed as barriers or facilitators of engagement for Aboriginal people. Quality assessment highlighted the need for research exploring the experiences of Aboriginal and Torres Strait Islander people living with disability and for more culturally appropriate and scientifically rigorous research. The findings provide guidance for policy makers and service providers in relation to supporting Aboriginal people living with disability. Points of interest: Aboriginal people living with a disability experience numerous barriers to positively engaging with disability services. The current literature that examines the lived experience of Aboriginal people living with a disability is limited in scope and quality. Aboriginal and Torres Strait Islander access and engagement with disability services may best be facilitated through the consideration of Aboriginal cultural beliefs, individual cultural needs, and Aboriginal perspectives of health. There is a need for disability services to become more culturally aware and more inclusive of Aboriginal cultural understandings to better inform inclusive policy and practice. The study recommends more collaborative research into the lived experience of Aboriginal people living with a disability, particularly relating to the way that inclusion can improve wellbeing and engagement with support services.